Preparation and Characterization of Graphene Oxide from Rice Husk - Atina Khoiron Nisa; Ganden Supriyanto; Wan Aini Wan Ibrahim (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2023)
Preparation and characterization of Graphene Oxide (GO) Fe3O4 nanocomposite has been done. The characterized by XRD showed that graphite,GO and GO-Fe3O4 were amorph. Characterized by FTIR showed that there were a distinctive vibration bands of C-O,C=O, C=C, and OH, and additional bands belong to Fe-O dan Fe-C for the GO-Fe3O4. FESEM analysed showed that GO have smooths and sheets, and fill the wrinkled circle on the surface GO was showed presence of Fe3O4. The diameters of Fe3O4 was 39 nm. Atoms distribution Fe, C, and O of Fe3O4 on the GO sheets showed 15 %. D-band and G-band of GO were 1331 cm-1 dan 1570 cm-1 and D-band of GO-Fe3O4 were 1331 cm-1 based on analyzed using Raman spectroscopy.